Reconstrucuting Gearing Ratio and Digital Base Service Rates to Mitigate Financial Risk for the Indonesian Credit Guarantee Industry’s Sustainability - Hari Tohar Muljono; Tri Ratnawati (International Conference of Innovation and Community Engagement, 2024)
This research examines the role of the credit guarantee industry in supporting the growth of MSMEs in Indonesia through guarantee programs that aim to reduce information asymmetry between banks and MSMEs. Using structured interview methods and data triangulation techniques from various sources, this study analyzes the management of gearing ratios and tariff risks that significantly impact the financial stability of guarantee institutions. The analysis results with NVIVO 12 reveal digital transformation’s importance in efficiency and transparency in risk management. This research also produces a digitalization design for the Program Gearing Ratio (PGR) and offers practical solutions through SWOT analysis to improve the guarantee capacity and sustainability of the industry. The findings contribute to the literature by proposing an integrated internal audit approach for financial risk mitigation in the credit guarantee industry.